-5x+6x+15-3x=-3

Simple and best practice solution for -5x+6x+15-3x=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+6x+15-3x=-3 equation:


Simplifying
-5x + 6x + 15 + -3x = -3

Reorder the terms:
15 + -5x + 6x + -3x = -3

Combine like terms: -5x + 6x = 1x
15 + 1x + -3x = -3

Combine like terms: 1x + -3x = -2x
15 + -2x = -3

Solving
15 + -2x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -2x = -3 + -15

Combine like terms: 15 + -15 = 0
0 + -2x = -3 + -15
-2x = -3 + -15

Combine like terms: -3 + -15 = -18
-2x = -18

Divide each side by '-2'.
x = 9

Simplifying
x = 9

See similar equations:

| 200x+7000000=170x+8200000 | | -11r=-32 | | x7/10=332 | | 5h+17h-19=20h+11 | | J+19=28 | | -13s=14-15s | | 5x-4+7x-64+120+6x-8+4x+15+3x+31+135=900 | | 100k=100 | | 11=-1+3s | | Y+18=28 | | 10r=-60 | | 10-6n=n-4 | | 113-(5x+16)=5(x+4)+x | | 3(2z+7)-2(2x-1)=17 | | z/6-7=-4 | | 5(7k-3)+3=31-81k | | 2r-18=10+4r | | S-19=24 | | 2x-15=6x+17 | | (x^3-4x^2-12x)=0 | | 11(y+5)=77 | | 12x=x^2+35 | | 60x+40y=2040 | | -m/9=1 | | (X-46)+(x+4)=90 | | 32x+40y=1200 | | 0.2k=-15 | | 30x=9 | | 2a(a-1)(3a-1)=0 | | 80x=-60 | | -7y-4=-3(y-4) | | -t/7=2 |

Equations solver categories